Eco-Friendly PVA/Starch/Rice Husk Char Coating For Controlled Release Fertilizers - Thi Lien Nguyen; Minh Ngoc Truong; Thanh Binh Le (Journal of Technical Education Science, 2024)
This research explores the development of a novel slow-release fertilizer coating composed of polyvinyl alcohol (PVA), tapioca starch, and modified rice husk char. The study focuses on the optimal production of rice husk char at 600°C, which facilitates enhanced silica and reduced carbon contents, improving its functional properties in the coating matrix. The incorporation of rice husk char into the PVA/starch blend significantly alters the film’s structural and chemical characteristics, as confirmed by FTIR analysis, which showed increased Si-O bonding. The coatings effectively reduced moisture absorption by approximately 50% in comparison to uncoated di-ammonium phosphate (DAP) granules, demonstrating superior protective qualities. Additionally, nutrient release profiles indicated a controlled release over 24h, which is critical for reducing environmental leaching. These results underscore the potential of using rice husk char in biopolymer coatings to enhance the environmental performance of fertilizers, offering a sustainable approach to agricultural management.